Impact of the e-prescribing system on the incidence and nature of drug-related problems in children in a Saudi hospital. (5th June 2019) - AlAzmi, Aeshah A; AlHamdan, Hani; Ahmed, Omaima; Tomlin, Stephen; Rashed, Asia N
Abstract: Objectives: To determine the impact of a computerised physician order entry (CPOE) system on the drug-related problems' (DRPs) incidence and characteristics in hospitalised children in a Saudi hospital, and to compare DRPs incidence pre-/post-CPOE implementation. Methods: An observational study. DRPs were identified by pharmacists, reviewing children's (0-14 years) medical records on CPOE system, in paediatric wards and/or attending emergency department. DRPs preventability and severity were assessed. Results: A total of 657 paediatric patients were included, with 235 (35.8%) experienced 328 DRPs, majority were preventable (99.7%, 327). Difference in DRP incidence pre- and post-CPOE implementation (44.8% versus 35.8%, P < 0.01) was significant. Conclusion: The CPOE system has significantly reduced DRPs incidence in children in the study hospital.